Corylus avellana “Nocciola Piemonte”: metabolomics focused on polar lipids and phenolic compounds in fresh and roasted hazelnuts - Cerulli, Antonietta; Napolitano, Assunta; Olas, Beata; Masullo, Milena; Piacente, Sonia (Frontiers in Plant Science, 2023)
The common hazel plant (Corylus avellana L., Betulaceae) is one of the most popular tree nuts, widespread in Europe and Asia. In Italy there are different cultivars among which the cultivar affording the valuable hazelnut "Tonda Gentile Trilobata", also known as "Tonda Gentile delle Langhe", covered by the Protected Geographical Indication (PGI) label "Nocciola Piemonte" (NP), known for its sweetness, cooked-bread aroma and low intensity of the burnt aroma. In order to obtain a detailed and in-depth characterization of the polar fraction of fresh (NPF) and roasted (NPR) kernels of "Nocciola Piemonte", analysis of the n-butanol extracts by liquid chromatography coupled to electrospray ionization and high-resolution mass spectrometry (LC-ESI/HRMS) was carried out. The evaluation of accurate masses, characteristic fragmentation patterns, chromatographic behavior, and literature data allowed to ascertain the presence of phenolic compounds and multiple classes of polar lipids including phospholipids, glycolipids, sphingolipids, and oxylipins. The analysis by liquid chromatography combined with tandem mass spectrometry (LC-MS/MS) of the quantitative distribution of the most representative polar lipids in NPF and NPR highlighted in the latter fraction a lipid content three times higher than in NPF, evidencing lyso-phospholipids and phospholipids as the most represented lipid classes in both NPF and NPR, together accounting for 94 and 97% of the considered lipids, respectively. Moreover, to unambiguously identify the phenolic compounds highlighted by the LC-ESI/HRMS profiles, they were isolated from the n-butanol extract and characterized as flavonoid and diarylheptanoid derivatives by NMR experiments. Finally, the ability of the isolated compounds to exert radical scavenging activity and to inhibit the lipid peroxidation induced by H2O2 or H2O2/Fe 2+ was tested by Trolox Equivalent Antioxidant Capacity (TEAC) and thiobarbituric acid reactive substances (TBARS) assays, respectively. Quercetin 3-O-β-D-galactopyranosyl-(1→2)-β-D-glucopyranoside and myricetin-3-O-α-L-rhamnopyranoside showed the highest antioxidant activity, exhibiting TEAC values similar to that of quercetin, used as reference compound (2.00 ± 0.03 and 2.06 ± 0.03 mM vs 2.03 ± 0.03 mM, respectively). Moreover, most of the tested compounds were found to reduce lipid peroxidation induced by H2O2 and H2O2/Fe 2+ more than curcumin used as positive control, with myricetin-3-O-α-L-rhamnopyranoside determining 44.4 % and 34.1 % inhibition percentage, respectively.